How to Improve Developmental Tasks and Prevent Psychosocial Problems Due to the Covid-19 Pandemic in School-Age Children? - Ruliyani Manumba; Novy Helena Catharina Daulima; Yossie Susanti Eka Putri (Jambura Nursing Journal, 2023)
Psychosocial problems due to COVID-19 can threaten children who contribute to mental disorders in adulthood. Psychosocial problems in children due to the pandemic in children include fear, difficulty, anxiety, obsessive compulsive disorder, mood swings, depression, even thoughts of suicide. The purpose of writing this scientific paper is to find out the application of therapeutic group therapy and family psychoeducation in achieving work development tasks and preventing psychosocial problems due to the Covid-19 pandemic in school-age children. The method used is a case series by applying therapeutic group therapy and family psychoeducation to 19 school-age children. The results obtained indicate that therapeutic group therapy and family psychoeducation can improve the tasks and developmental aspects of school-age children and prevent the risk of psychosocial problems due to the COVID-19 pandemic. This action is recommended to promote development and prevent psychosocial problems due to the COVID-19 pandemic in school-age children.